Pemberdayaan IGI Rembang: Diseminasi Model Pembelajaran Differentiate Indirect Learning untuk Menumbuhkan Budaya Riset di Sekolah - Rusilowati, Ani; Marwoto, Putut; Sugianto, Sugianto; Sulhadi, Sulhadi; Widiyatmoko, Arif; Imron, Imron; Jalaluddin, Wahyu; Noviyatun, Siti; Nursidhi, Nursidhi (Jurnal Dharma Indonesia, 2024)
The era of educational revolution 4.0 and society 5.0 requires students to have research skills. An independent curriculum with a new learning paradigm enables the realization of student research skills and a research culture in schools. The current condition of students' research skills in Rembang is still low. Meanwhile, in Rembang there is the Indonesian Teachers Association (IGI) community which can be empowered to become partners in realizing a research culture in schools. It is necessary to provide teachers with learning models that can facilitate students doing research. through the application of the Differentiate Indirect Learning (DIF-IN-LE) learning model with a Science, Technology, Engineering and Mathematics (STEM) approach. The objectives of this service activity are (1) to equip IGI Rembang administrators in holding fun and meaningful training for teachers, (2) to equip teachers with the knowledge and skills to innovate in implementing the DIF-IN-LE learning model with a STEM approach, in fostering a research culture in students and school. The solution to the problems in this service is by applying training and facilitation methods to partner groups, so that they are skilled at designing and implementing the DIF-IN-LE learning model with a STEM approach for teachers in Rembang. Activity design uses the facilitation-based 4M Genre model (Genre 4M-F). The service activity plan consists of preparation, implementation and evaluation stages. The results of the activity show an increase in teachers' abilities in designing learning that can foster research skills for students